Enabling a rapid and just transition away from coal in China (2020)
As the world’s largest coal producer and consumer, China’s transition from coal to cleaner energy sources is critical for achieving global decarbonization. Increasing regulations on air pollution and carbon emissions and decreasing costs of renewables drive China’s transition away from coal; however, this transition also has implications for employment and social justice. Here, we assess China’s current coal-transition policies, their barriers, and the potential for an accelerated transition, as well as the associated environmental, human health, and employment and social justice issues that may arise from the transition. We estimate that the most aggressive coal-transition pathway could reduce annual premature death related to coal combustion by 224,000 and reduce annual water consumption by 4.3 billion m3 in 2050 compared with business-as-usual. We highlight knowledge gaps and conclude with policy recommendations for an integrated approach to facilitate a rapid and just transition away from coal in China.